Comparative Studies on Chinese and Western Civilizations - Yue, PAN (Springer Nature Singapore : Imprint: Springer, 2026)
This open access book compares Chinese and Western civilizations from multiple perspectives, and it mainly consists of three parts that respectively compare the Warring States and ancient Greece, the Qin and Han dynasties and ancient Rome, and the Central Plains of China and the Western Roman Empire in the face of incursions from neighboring ethnic groups. It explores the inner logic behind the different development paths of Chinese and Western civilizations, making a significant contribution to promoting communication and dialogue between the two. This book is of great help for scholars, students, and general readers interested in the comparative study of civilizations, as well as those seeking to foster cross-cultural understanding and dialogue.
Keywords: China -- History.; Ethnology -- Asia.; Culture.; Philosophy, Chinese.; Philosophy.; History of China.; Asian Culture.; Chinese Philosophy.; Intercultural Philosophy and Religious Traditions.